Hubungan Antara Dukungan Sosial Keluarga dengan Penerimaan Diri Individu yang Mengalami Asma - Utami, Ni Made Sintya Noviana; Widiasavitri, Putu Nugrahaeni (Jurnal Psikologi Udayana; Vol 1 No 1 (2013)DO - 10.24843/JPU.2013.v01.i01.p02, 2013)
Asthma is an inflammatory disease caused by narrowing of the respiratory tract. This disease can not be cured but its relapse can be controled. It will provide physiological and psychological impact to individual with asthma. That individual hardly tends to accept his or her self when diagnosed with  chronic disease. Family social support will be needed to cope with the hard situation faced by individual with asthma. According to that, researcher formulates the problem, is there relationship between family social support and self acceptance of individuals with asthma.   This research uses quantitative approach with correlation method. Samples in this research are 105 people suffer from asthma in Sanjiwani Hospital, Gianyar, who were chosen by systematic random sampling. The data are collected by questionnaire. Validity test of items of the family social support questionnaire shows there are 5 invalid items and 27 valid items from 32 items, and its reliability coefficient is 0,896. Validity test of items of the self acceptance questionnaire shows there are 12 invalid items and 30 valid items from 42 items, and its reliability coefficient is 0,899. Data analysis by Pearson’s product moment. Found coefficient correlation in this research is 0,687 with p value 0,000. Thus, there is positive relationship between family social support and self acceptance of individuals with ashtma.   Keywords : family social support, self acceptance